The questions and features of world-formation-terminology in arabic language (Journal of Oriental Studies, 2017)
In this article I have looked through the newspaper “Al-Ahram” theyears 2012 till 2013. They are the forms of types of using political termstheir way, of lexical, morphological structures in general these articles researchlanguage study theory.